Pengaruh Online Customer Review terhadap Online Purchase Decision (Survei pada Pengguna Bukalapak di Indonesia yang Tergabung dalam Grup Facebook Bukalapak) - Hanah Fatukha Rahmawati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
This research aims to obtain an overview and influence of online customer reviews on online purchase decisions among Bukalapak users. This research uses descriptive and verification methods with a quantitative approach. The population in this study amounted to 9,900 with a sample of 200 Bukalapak user respondents who are members of the Bukalapak Facebook group using a random sampling technique. The data is processed statistically using the Structural Equation Modeling (SEM) method. The findings in this study found that online customer review and online purchase decisions were in the high category. Online customer reviews have a positive and significant influence on online purchase decisions. These findings indicate that the application of online customer reviews can build and shape online purchase decisions for Bukalapak users. The credibility dimension in online customer reviews gives the biggest contribution in shaping online purchase decisions.